2011
DOI: 10.1371/journal.pone.0022690
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of Transgenic Powdery Mildew-Resistant Wheat by Naturally Occurring Insect Herbivores under Different Environmental Conditions

Abstract: A concern associated with the growing of genetically modified (GM) crops is that they could adversely affect non-target organisms. We assessed the impact of several transgenic powdery mildew-resistant spring wheat lines on insect herbivores. The GM lines carried either the Pm3b gene from hexaploid wheat, which confers race-specific resistance to powdery mildew, or the less specific anti-fungal barley seed chitinase and β-1,3-glucanase. In addition to the non-transformed control lines, several conventional spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Aphids in 2017 and 2018 were present, but not highly abundant with approximately 0.5 individuals per tiller. Similar aphid numbers, however, were reported from a field study with transgenic powdery mildew-resistant wheat conducted in 2008 and 2009 at the same field site in Zurich, Switzerland [16], which indicates that the aphid numbers in the present study were not extraordinary low.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Aphids in 2017 and 2018 were present, but not highly abundant with approximately 0.5 individuals per tiller. Similar aphid numbers, however, were reported from a field study with transgenic powdery mildew-resistant wheat conducted in 2008 and 2009 at the same field site in Zurich, Switzerland [16], which indicates that the aphid numbers in the present study were not extraordinary low.…”
Section: Discussionsupporting
confidence: 87%
“…Among the most important ones in Central Europe are cereal aphids, e.g., Rhopalosiphum padi (Linnaeus), Sitobion avenae (Fabricius), and Metopolophium dirhodum (Walker) , all Hemiptera: Aphididae [15]. Aphids have previously been deployed to study non-target effects of non-insecticidal GE plants, including mildew-resistant wheat [16,17,18], leaf-rust-resistant wheat [19], late-blight-resistant potato [20,21,22], and nematode-resistant potato [23]. For the present study, aphids were selected as test organisms for the following reasons: (1) They are abundant in the field and amenable for testing in the laboratory; (2) Changes in aphid abundance can indicate potential impacts on the food-web, but also on the capability of the plants to cope with biotic stress; (3) Aphids feed on phloem sap and might therefore respond to changes in assimilate and protein supply and expression of regulators related to sugar signaling and amino-acid synthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our study on AMF and pseudomonads revealed similar results as studies on other non-target organisms performed by different groups in the frame of the same field experiments. These studies showed no relevant impact of the pm3b on the abundance of aphids, the cereal leaf beetle Oulema malanopus or the wheat stem fly Chlorops pumilionis [49], on the dipterans Drosophila melanogaster and Megaselia scalaris [50], on the annelid Enchytraeus albidus [51], on aphid-parasitoid food webs [52], [53] and on soil decomposition activity and soil fauna [54].…”
Section: Discussionmentioning
confidence: 97%
“…Other research projects within the Consortium have studied agronomic properties of the wheat lines in common agricultural trials, gene × abiotic environment interactions in the glasshouse and in the field [31], disease resistance and gene expression [32] and the impact of the GM lines on other organisms [33][35].…”
Section: Introductionmentioning
confidence: 99%